2018
DOI: 10.3233/wor-182748
|View full text |Cite
|
Sign up to set email alerts
|

After hours teleworking and boundary management: Effects on work-family conflict

Abstract: The findings suggest that teleworking after hours is not as problematic in terms of work-family conflict as has been reported in previous studies. Furthermore, in order to prevent high levels of work-family conflict, it is seemingly beneficial to avoid work interruptions during nonwork behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 50 publications
3
47
0
12
Order By: Relevance
“…Today, employees can have access to their private lives from their workplaces to a greater extent than ever before. This possibility of combining work and non-work responsibilities is reported by employees as one major advantage of the increased flexibility facilitated by ICT [13][14][15][16]. However, research on smartphone and ICT use has also consistently shown that the boundaries between work and family life have become permeable [17], which may increase the risk of experiencing imbalance between work and family life [18].…”
Section: Introduction and Aimmentioning
confidence: 99%
“…Today, employees can have access to their private lives from their workplaces to a greater extent than ever before. This possibility of combining work and non-work responsibilities is reported by employees as one major advantage of the increased flexibility facilitated by ICT [13][14][15][16]. However, research on smartphone and ICT use has also consistently shown that the boundaries between work and family life have become permeable [17], which may increase the risk of experiencing imbalance between work and family life [18].…”
Section: Introduction and Aimmentioning
confidence: 99%
“…A maior flexibilidade favorece assim alguns funcionários, de modo que estes conseguem melhor coordenar as suas responsabilidades familiares e passar mais tempo com o agregado familiar-daí que, simultaneamente, possa aliviar conflitos familiares. Os trabalhadores ficam mais satisfeitos e produtivos se tal se evitar; logo deveria ser do interesse do empregador atingir tal patamar (36). Um desequilíbrio entre a vida profissional e familiar pode gerar ansiedade em qualquer funcionário.…”
Section: Vantagensunclassified
“…Trabalhar em casa fora do horário laboral poderá ser encarado para alguns como algo positivo, dado sentirem que têm mais liberdade para decidir quando trabalhar, gerindo com mais facilidade todas as suas responsabilidades (36). Para além disso, parece que empregos que exijam muitas horas de trabalho, podem ser melhor executados em regime de TT, dado o funcionário ter mais autonomia e controlo para gerir as tarefas; ou seja, trabalham mais horas, na intensidade que preferem, sem as distrações que possam existir no local de trabalho presencial (45).…”
Section: Vantagensunclassified
See 2 more Smart Citations